Product review of the rotavirus vaccines ROTASIIL, ROTAVAC, and Rotavin-M1 - Annika Skansberg; Molly Sauer; Marissa Tan; Mathuram Santosham; Mary Carol Jennings (Taylor & Francis Group, 2021)
Rotavirus is the leading cause of severe dehydrating gastroenteritis and death due to diarrhea among children under 5, causing over 180,000 under-5 deaths annually. Safe, effective rotavirus vaccines have been available for over a decade and are used in over 98 countries. In addition to the globally available, WHO-prequalified ROTARIX (GSK) and RotaTeq (Merck), several new rotavirus vaccines have attained national licensure - ROTAVAC (Bharat Biotech) and ROTASIIL (Serum Institute of India), licensed and manufactured in India and now WHO-prequalified, and Rotavin-M1 (PolyVac), licensed and manufactured in Vietnam. In this review, we summarize the available clinical trial and post-introduction evidence for these three new orally administered rotavirus vaccines. All three vaccines have demonstrated safety and efficacy against rotavirus diarrhea, although publicly available preclinical data are limited in some cases. This expanding product landscape presents a range of options to optimize immunization programs, and new presentations of each vaccine are currently under development.